Engagement in binge eating and fasting associated with poorer sleep quality in an online sample of adults - Leah A. Irish; Kara A. Christensen Pacella; Maegan B. Nation; Rachel D. Barnes (Journal of Eating Disorders, 2024)
Abstract Objectives Both disordered eating and disturbed sleep represent significant threats to mental health. Accumulating evidence suggests that disordered eating behaviors and sleep problems co-occur. A majority of current research, however, has focused on these behaviors as components of eating disorder diagnoses, rather than investigating the independent associations of transdiagnostic disordered eating behaviors and sleep. The present study sought to examine fasting, binge eating, self-induced vomiting, laxative or diuretic misuse, and driven exercise as predictors of sleep quality complaints. Method An online sample of 648 U.S. adults completed the Eating Disorder Examination - Questionnaire, the Pittsburgh Sleep Quality Index, and the Patient Health Care Questionnaire-2 as part of a larger parent study. Results Results of a hierarchical linear regression revealed that, collectively, disordered eating behaviors predicted worse sleep quality [R2 = 0.30, F(7, 640) = 31.21, p < .001], and that both binge eating and fasting, but not other compensatory behaviors, accounted for unique variance in sleep quality after controlling for BMI and depression. Conclusions Overall, findings suggest that transdiagnostic disordered eating behaviors are associated with sleep quality complaints. Improved understanding of the specific relationships between individual eating behaviors and sleep characteristics can help refine the identification of individuals at high risk for sleep disturbance and address the potential reciprocal influence of sleep quality on disordered eating behaviors.